2016
DOI: 10.1016/j.krcp.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between serum soluble Klotho and carotid intima–media thickness and left ventricular dysfunction in hemodialysis patients

Abstract: BackgroundThe aim of our study was to assess the relationship between soluble Klotho (s-Klotho) and carotid intima–media thickness (CIMT) and left ventricular (LV) dysfunction in hemodialysis (HD) patients.MethodsThis is a cross-sectional study conducted on 88 patients with end-stage renal disease on regular HD. Serum levels of calcium, phosphorus, parathyroid hormone, and C-reactive protein were measured. The serum levels of s-Klotho and fibroblast growth factor-23 (FGF-23) were measured using an Enzyme linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
2
19
1
2
Order By: Relevance
“…We studied the correlation between serum klotho levels and both pulmonary hypertension and LVH, and we found that patients with lower serum klotho levels showing a trend toward presence of pulmonary hypertension and LVH. Our findings are in agreement with a recently published study that showed that patients with a low sKlotho were more often associated with increased Carotid intimamedia thickness and LV dysfunction [19] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We studied the correlation between serum klotho levels and both pulmonary hypertension and LVH, and we found that patients with lower serum klotho levels showing a trend toward presence of pulmonary hypertension and LVH. Our findings are in agreement with a recently published study that showed that patients with a low sKlotho were more often associated with increased Carotid intimamedia thickness and LV dysfunction [19] .…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with many studies in CKD patients [19,22] Limitations of our study are several. First, the number of evaluated patients is rather low.…”
Section: Discussionsupporting
confidence: 92%
“…A multivariable linear regression model showed serum Klotho had a significant inverse association with LVMI. But in a more recent cross-sectional study including 88 patients with end-stage renal disease on regular hemodialysis, s-Klotho showed significant association with LVEF, but not with LVM and LVMI [10]. Similarly, Buiten et al [25] also failed to find a relationship between serum s-Klotho and LVMI in 127 dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and his colleagues [9] analyzed 2,101 CKD patients (the mean estimated glomerular filtration rate was 53.0 ± 30.7 mL/min/1.73 m 2 ) and reported that serum Klotho was an independent biomarker of left ventricular mass index (LVMI). But another cross-sectional study with 88 MHD patients showed that s-Klotho was significantly associated with left ventricular ejection fraction (LVEF), but not with LVMI [10]. …”
Section: Introductionmentioning
confidence: 99%
“…К настоящему времени большинство исследований роли s-Klotho проведено в эксперименте или на попу-ляции лишь для диализных больных [5,6]. У пациентов с додиализными стадиями роль белка s-Klotho изучена значительно хуже.…”
Section: актуальные вопросы внутренних болезней введениеunclassified